2022
DOI: 10.1021/acs.jafc.2c00414
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of ATP-Binding Cassette Transporters Involved in the Detoxification of Abamectin in Rice Stem Borer, Chilo suppressalis

Abstract: Chilo suppressalis has developed high levels of resistance to abamectin in many areas of China, while the underline resistance mechanisms are largely unclear. ATP-binding cassette (ABC) transporters function in transporting a large diversity of substrates including insecticides and play important roles in the detoxification metabolism of insects. In this study, synergism bioassay revealed that the ABC transporters were involved in the detoxification of C. suppressalis to abamectin. Six ABC transporter genes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
(132 reference statements)
1
10
0
Order By: Relevance
“…A similar situation has been reported in which the detoxification and transport of abamectin in C. suppressalis were related to ABCC, ABCE, and ABCH subfamily genes …”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…A similar situation has been reported in which the detoxification and transport of abamectin in C. suppressalis were related to ABCC, ABCE, and ABCH subfamily genes …”
Section: Discussionsupporting
confidence: 83%
“…PhABCC4 -expressing oocytes were able to directly excrete 3 H-ivermectin, indicating that the ABC transporter mediates the resistance of Pediculus humanus to ivermectin . The cytotoxicity assay of Sf9 cells indicated that ABCC8 , ABCE1 , and ABCH1 participate in the detoxification and transport of abamectin in Chilo suppressalis . In our recent research, the upregulated ABC transporter genes in A.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…SfHO protein was expressed in the Bac-to-Bac baculovirus expression system as previously described . Briefly, the ORF of SfHO was amplified using primers containing Bam HI and Eco RI restriction sites (Table ) and ligated to pFastBac-HTb (Thermo Fisher Scientific, Waltham, MA, U.S.A.) using the ClonExpress II One Step Cloning Kit (Vazyme, Nanjing, China).…”
Section: Methodsmentioning
confidence: 99%